A Case Study Evaluating Youth Acceptability of Using the Connect – a Sexuality Education Game-Based Learning Program. Issue 1 (2nd January 2022) - Esquivel, Christi H.; Wilson, Kelly L.; Garney, Whitney R.; McNeill, Elisa Beth; McMaughan, Darcy Jones; Brown, Sydney; Graves-Boswell, Taylor
Abstract: Game-based learning offers an interactive and effective way to teach health content and skills. This article discusses feasibility testing of Using the Connect (UTC), an innovative, game-based sexuality education program to evaluate its acceptability among youth. Utilizing mixed methods in a single case study design, qualitative and quantitative data was collected from youth (surveys, facilitated discussions, and observations). Qualitative data triangulated quantitative findings that youth liked the program design, felt the games and content were relatable, and learned knowledge and skills around adolescent development, accessing information, communication, and making healthy decisions through playing the games. Overall, UTC was highly acceptable to the youth; they had fun and learned information and skills. Not only would most participants recommend the program to friends, all reported they would participate in the program again and use the information they learned in the future.